SERAT BALEWARNA: JAWA MENOLAK JAWA KOLONIALISASI ATAUKAH RASIONALISASI PENGETAHUAN ARSITEKTUR JAWA? - Josef Prijotomo (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2002)
Perceptual ambiguity is a state of thinking that disturbs the either-or mode of knowledge. It causes one to face with the condition of two possible correct knowledges. This state of thinking, however, might be advantageous and contributive positively. Robert Venturi's dictum both-and is just one example of taking the advantageous of this perceptual ambiguity. Taking one Jawanese corpus titled Serat Balewarna, this study tries to present the practice of either-or mode of knowledge in Jawa around the 1920-s. A critical examination upon its content shows that the rational-universal knowledge had only becomes one lethal weapon against the Jawanese architectural knowledge. Toward thee end of the examination, this paper proposes to locate the jawanese architecture in a state of perceptual ambiguity. This re-location will open the way to allow the Jawanese architectural knowledge enter the world of discourse of knowledge in architecture. Abstract in Bahasa Indonesia : Ambiguitas perseptual adalah sebuah keadaan berpikir yang memusingkan pengetahuan ini-itu (either-or), mengingat keadaan itu memaksa seseorang untuk memilih satu dari dua kebenaran pengetahuan. Dari sisi lain, ambiguitas perseptual ternyata dapat menjadi keadaan yang menguntungkan dan memberi sumbangan yang positif. Diktum Robert Venturi